Recent Advancement and Emerging Applications of Lignin - Tanu Mittal; Rishi Kant; Yogesh Bhalla; Mohit Kumar Goel (Universitas Gadjah Mada, 2024)
Lignin is a significant renewable natural energy resource these days, used as an environmentally acceptable and sustainable alternative fossil fuel feedstock in a huge possibility of value-added products. Lignin is a polymeric molecule that possesses an aromatic unit structure, together with cellulose, and is a main component of the cell walls of plants. It is the byproduct of agriculture residues and biorefinery products and can be extracted from paper-pulp industries. Properties of lignin may differ depending on the extraction method and source and also on an aromatic ring as the main constituent of lignin in the structure. This rare composition of lignin makes it more valuable, allowing for value-added applications such as in the field of storage devices and energy harvesters. This review focuses on derivatives of lignin, structure and composition sources and characteristics, and its sustainable emerging application in various fields are discussed.